2017
DOI: 10.1002/poc.3787
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfoxide/deep eutectic solvents mixtures as media in the reaction of 1‐fluoro‐2,4‐dinitrobenzene with piperidine: A solvent effect study

Abstract: Aromatic nucleophilic substitution reaction of 1‐fluoro‐2,4‐dinitrobenzene with piperidine was kinetically investigated in ethylene glycol‐choline chloride and glycerol‐choline chloride as 2 deep eutectic solvents (DESs) mixed with dimethyl sulfoxide, in whole mole fractions, at room temperature. The investigation of the reaction in different concentrations of the piperidine shows that the reaction follows the base‐catalyzed mechanism. The measured rate coefficients of the reaction demonstrated a sharp decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…These {glyceline+DMSO} mixtures, which are stable over the entire composition range for temperatures T ≥ 293.15 K, are of practical interest due to their significantly lower viscosity compared to neat glyceline. Recently, DESs mixed with DMSO have been considered as operative media for substitution reactions of para- and meta-substituted anilines with 1-fluoro-2,4-dinitrobenzene. , The employed DESs were 1:2 ChCl/ethylene glycol, usually called ethaline, , and glyceline . The analysis of the solvent effect on the reaction kinetics showed that the reactants and intermediate products are preferentially solvated by DES components and DMSO, respectively, which can be used as a factor of controlling the reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…These {glyceline+DMSO} mixtures, which are stable over the entire composition range for temperatures T ≥ 293.15 K, are of practical interest due to their significantly lower viscosity compared to neat glyceline. Recently, DESs mixed with DMSO have been considered as operative media for substitution reactions of para- and meta-substituted anilines with 1-fluoro-2,4-dinitrobenzene. , The employed DESs were 1:2 ChCl/ethylene glycol, usually called ethaline, , and glyceline . The analysis of the solvent effect on the reaction kinetics showed that the reactants and intermediate products are preferentially solvated by DES components and DMSO, respectively, which can be used as a factor of controlling the reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…FDNB is a good candidate for a nucleophilic aromatic substitution with the addition‐elimination mechanism. In continuing our recent study of solvent effects on organic reactions and similar studies, we were interested in studying effects of mixtures on DESs with molecular solvents. The reaction of FDNB with some substituted anilines was studied at 25°C in binary mixtures of ethaline and DMSO mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…However, the solute-solvent interactions have been widely investigated by using the physical property Y as a solvatochromic parameter, 27,[31][32][33] the use of this model as a nonlinear relationship between activation free energy of chemical reactions and solvent composition (non-LFER) has demonstrated interesting results. 20,33,34 Equation 6 was applied for log k A , and the results are summarized in Table 4. Statistical parameters and good agreement shown in Figure 3 confirm the ability of Equation 6 in reproducing the reaction rate coefficients.…”
Section: Preferential Solvationmentioning
confidence: 99%
See 2 more Smart Citations